2010
DOI: 10.1158/1078-0432.ccr-09-1764
|View full text |Cite
|
Sign up to set email alerts
|

Lapatinib Restores Hormone Sensitivity with Differential Effects on Estrogen Receptor Signaling in Cell Models of Human Epidermal Growth Factor Receptor 2–Negative Breast Cancer with Acquired Endocrine Resistance

Abstract: Purpose: Acquired endocrine resistance in estrogen receptor (ER)α+/human epidermal growth factor receptor 2-negative (HER2−) breast cancer has been associated with modest adaptive increases in HER2, although exactly how aberrant HER2 signaling affects the ERα pathway is poorly understood. We investigated (a) whether the epidermal growth factor receptor/HER2 inhibitor lapatinib could restore endocrine responsiveness in cell models of acquired endocrine resistance with modest increases in HER2, and (b) the natur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
54
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 33 publications
9
54
0
Order By: Relevance
“…Downregulation of RET re-sensitized TAM R -1 cells to the anti-proliferative effects of 4-OHtamoxifen. Interestingly, TAM R -1 cells also show elevated level of phosphorylated ErbB2 and the magnitude of re-sensitization to tamoxifen in the RET siRNA-treated cells was equivalent to that previously reported for the ErbB2 inhibitors AG825 and lapatanib (Pancholi et al, 2008;Leary et al, 2010). Consequently, these data presented here provide evidence that RET is Figure 3 RET signaling induces ERa Ser118 and Ser167 phosphorylation through mTOR.…”
Section: Discussionsupporting
confidence: 85%
“…Downregulation of RET re-sensitized TAM R -1 cells to the anti-proliferative effects of 4-OHtamoxifen. Interestingly, TAM R -1 cells also show elevated level of phosphorylated ErbB2 and the magnitude of re-sensitization to tamoxifen in the RET siRNA-treated cells was equivalent to that previously reported for the ErbB2 inhibitors AG825 and lapatanib (Pancholi et al, 2008;Leary et al, 2010). Consequently, these data presented here provide evidence that RET is Figure 3 RET signaling induces ERa Ser118 and Ser167 phosphorylation through mTOR.…”
Section: Discussionsupporting
confidence: 85%
“…In fact, lapatinib was recently shown to restore endocrine sensitivity in breast cancer cells with acquired resistance because of modest adaptive upregulation of HER2 (Leary et al, 2010). Moreover, lack of p53 and phosphorylated HER3 have been associated with better lapatinib responses in HER2-overexpressing patients; HER2-overexpressing tumors also exhibit increased expression of heregulin/ neuregulin (Johnston et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These findings might reflect acquired resistance to tamoxifen treatment in the adjuvant setting of HR positive BC patients. It has been recently reported that acquired endocrine resistance in positive ER/negative HER2 BC may be associated with an adaptive increase in HER2, although exactly how aberrant HER2 signaling affects the ERa pathway is poorly understood (27). The discordance between PBC and MBC reported in our series resembles other retrospective and prospective studies PAFAHIB1 PMP22 TOM1L2 WSB1 WSB1 WSB1 NOS2A TRAF4 CPD RNF135 PEX12 NEUROD2 ER882 ER882 ER882 RARA TOP2A TOP2A TOP2A BRCA1 BRCA1 SGCA GH1 METRNL PAFAHIB1 PMP22 TOM1L2 WSB1 NOS2A TRAF4 CPD RNF135 PEX12 NEUROD2 HER2 RARA TOP2A BRCA1 SGCA GH1 METERNL 14 12 10 8 6 4 2 0 Ratio PAFAHIB1 PMP22 TOM1L2 WSB1 WSB1 WSB1 NOS2A TRAF4 CPD RNF135 PEX12 NEUROD2 ER882 ER882 ER882 RARA TOP2A TOP2A TOP2A BRCA1 BRCA1 SGCA GH1 9,12,14,28).…”
Section: Discussionmentioning
confidence: 99%